Dual role of Magnesium as a catalyst and precursor with enriched boron in the synthesis of Magnesium diboride nanoparticles - Ahmad, P.; Khandaker, Mayeen Uddin *; Jamil, S.; Rehman, F.; Muhammad, N.; Ullah, Z.; Rauf Khan, M.; Khan, G.; Alotaibi, M. A.; Alharthi, A. I.; Din, I. U.; Hussain, F.; et al. (Elsevier, 2020)
Nano-scale powder of Magnesium (Mg) is found to play the dual role of catalyst and precursor with Boron-10 (10B) in the synthesis of Magnesium diboride nanoparticles (Mg10B2NPs) at 800 °C. Catalytically, Mg softens and melts enriched Boron at a relatively lower temperature than its actual boiling point. As a precursor, it reacts with enriched Boron and forms the Mg10B2 compound. The nano-size catalyst and precursors help to grow the as-formed Mg10B2 compound in the form of nanoparticles. The shape or morphology of the synthesized Mg10B2NPs is revealed via field emission scanning electron microscopy (FESEM). Energy dispersive x-ray (EDX) spectroscopy has been performed to spot the elemental composition, whereas, X-ray diffraction (XRD), and X-ray photoelectron spectroscopy (XPS) are used to verify the composition and study the phase of the synthesized particles.